Growth Effects of Public Expenditure on the State and Local Level: Evidence from a Sample of Rich Governments - Christoph A. Schaltegger; Benno Torgler (Center for Research in Economics, Management and the Arts (CREMA), 2004)
There is a vast empirical literature investigating the relationship between government size and economic growth. But the empirical evidence of growth effects of public expenditure using cross-country regres-sions is still inconclusive. According to a number of authors this is not surprising since the negative rela-tionship only applies for rich countries with a large public sector. Restricting their analysis on rich coun-tries only they can show the predicted negative impact. Naturally, a selection of a sub-sample of rich countries is always somewhat arbitrary. Another possibility is to concentrate on governments within a rich country. However, only few studies investigate the effect of state and local spending on economic growth. This paper concentrates on the relationship between public expenditure and economic growth within a rich country using the full sample of state and local governments from Switzerland over the 1981-2001 period. The general finding is a fairly robust negative relationship between government size and economic growth. However, in contrast to public spending from operating budgets there is no significant impact on economic growth by expenditure from capital budgets.
Keywords: E62; H20; O23; 330; Economic Growth; Government expenditure; Public Sector